2019
DOI: 10.1029/2019jd030799
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dust in East Asia by CESM and Sources of Biases

Abstract: East Asian dust has a significant impact on regional and global climate. In this study, we evaluate the spatial distributions and temporal variations of dust extinction profiles and dust optical depth (DOD) over East Asia simulated from the Community Earth System Model (CESM) with satellite retrievals from Luo, Wang, Ferrare, et al. (2015, https://doi.org/10.1029/2002JD002775), Luo, Wang, Zhang, et al. (2015, https://doi.org/10.1002/2014GL062111) (L15), Yu et al. (2015, https://doi.org/10.1016/j.rse.2014.12.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 80 publications
(151 reference statements)
2
35
0
Order By: Relevance
“…The three models also overestimate DOD over Northwest China due to the overestimation of dust emission in MAM, JJA, and SON. Wu et al (2019) showed that CESM1 with K14 dust emission scheme better agrees with CALIOP observations in Northwest China. Since the source functions used in the four models are all zeros north to 60°N, the four models don't produce any dust emissions in NH high-latitude regions, while ground observations indicate considerable local dust sources.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The three models also overestimate DOD over Northwest China due to the overestimation of dust emission in MAM, JJA, and SON. Wu et al (2019) showed that CESM1 with K14 dust emission scheme better agrees with CALIOP observations in Northwest China. Since the source functions used in the four models are all zeros north to 60°N, the four models don't produce any dust emissions in NH high-latitude regions, while ground observations indicate considerable local dust sources.…”
Section: Discussionmentioning
confidence: 61%
“…8d, h, and l. We note that there are considerable differences between satellite retrievals from L15 and Y15. Dust extinction from L15 is larger in the upper troposphere and lower in the lower troposphere than that from Y15, which is due to different dust identification and separation methods (Wu et al, 2019).…”
Section: Dust Extinctionmentioning
confidence: 94%
See 1 more Smart Citation
“…Dust emission is the first and foremost process for model improvements of dust cycle (Shao, 2008;Shao et al, 2011). Improving dust emission not only lies in the development of dust emission scheme but also in its implementation into climate models (e.g., Shao, 2008;Wu et al, 2016;Wu et al, 2019). For example, different dust emission schemes with specific land cover datasets and criteria for the occurrence of dust emission are adopted in the models (Table 1 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Chem. Phys., 19, 12025-12049, https://doi.org/10.5194/acp-19-12025-2019, 2019 Randles, C. A., Silva, A. M. d., Buchard, V., Colarco, P. R., Darmenov, A., Govindaraju, R., Smirnov, A., Holben, B., Ferrare, R., Hair, J., Shinozuka, Y., and Flynn, C. 108, 4416, https://doi.org/10.1029/2002jd002775, 2003. https://doi.org/10.5194/acp-2020-179 Preprint. Discussion started: 3 April c Author(s) 2020.…”
Section: Discussionmentioning
confidence: 99%